EFEKTIVITAS PENGGUNAAN Piper batle L. UNTUK MEMPERPANJANG MASA SIMPAN TELUR AYAM RAS - Darwanto, Agus; Hanum Aulia Sansabrina , Elsa; Cita Sutarto, Intantiara (Jurnal Inovasi Daerah, 2023)
The consumption of chicken eggs capita per annual in Indonesia has been increasing rapidly from year to year. It shows that the demand for eggs is very high. Egg is a popular source of protein for Indonesian people. However, the quality of eggs will decrease over time if they are stored for a long time. This study aims to analysis the effectiveness of using betel leaves to extend the shelf life of eggs and their effect on protein and fat content. Data collection methods were carried out experimentally. Data analysis methods were carried out using statistical analysis, analysis of variance, BNT/LSD analysis, and regression. Wrapping eggs with betel leaves can extend the shelf life of eggs, even better than eggs stored in the refrigerator for 9 days or more. Based on the analysis of the anova test, it was proven that there was a significant difference between the use of betel leaves and other treatments. The cause is thought that betel leaves have good antibacterial and antifungal activities. The effect of betel leaves on egg quality is 43.9%. Similarly, the effect of wrapping eggs with betel leaves on protein and fat content. Betel leaves can prevent the decrease in protein and total fat content in eggs from a protein decrease of 50% to 49.52% and a fat decrease from 65.8% to 32.8%.